Sosialisasi Lingkungan Pertambangan Berkelanjutan pada Masyarakat di Desa Ngapainia Kecamatan Langgikima Kabupaten Konawe Utara - Endang Abubakar; La Ibal (Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2023)
Mining activities have positive and negative impacts socially, economically and ecologically so as to create jobs and economic growth, especially for communities around mining. This community service activity was carried out in Ngapainia Village, Langgikima District, North Konawe Regency, Southeast Sulawesi Province by involving the community. The purpose of this service activity is to find out the socialization of the sustainable mining environment to the people in Ngapainia Village, Langgikima District, North Konawe Regency. The socialization carried out regarding mining activities, the impacts they cause, the principles of good and correct mining, ecological principles, the environment, environmental components. Apart from that, socialization was also carried out in the form of the concept of Good Mining Practices, Environmental Damage Control, and Socio-Economically and Ecologically Sustainable Mining Environment. The results of the socialization show that the community is enthusiastic and appreciates this activity and is interested in applying this appropriate technology.